Contradiction or Coordination? Spatial Heterogeneity Between Urbanization and Green Development in the Yangtze River Delta Region, China - Ying Jing; Yuxuan Yang; Yue Lang; Qing Miao (Urban Science)
With the rapid acceleration of socio-economic development, the potential contradiction between urbanization and green development becomes a concerning issue. Ascertaining their relationship is conducive to new-type urbanization transformation and ecologically sustainable development. To reveal their complex and dynamic relationship, this study first calculates urbanization and green development by a linear weighting method and the coupling coordination degree (CCD) model. Then, the local spatial autocorrelation method is adopted to explore the CCD spatial effect on the Yangtze River Delta Region (e.g., Shanghai Municipality, and Jiangsu, Zhejiang, and Anhui provinces) in China. The results reveal three key findings as follows: (1) Overall, the 41 cities within the Yangtze River Delta Region (YRDR) exhibited a relatively high level of coordination, albeit with notable regional disparities. (2) Several cities experienced unbalanced development, with either green development lagging behind urbanization or vice versa. (3) Spatial clustering patterns indicate that neighboring cities influence one another, highlighting the importance of regional collaboration. These findings provide critical insights for policymakers to enhance sustainable urban planning and foster balanced development across the region.